2013
DOI: 10.1038/nature12108
|View full text |Cite
|
Sign up to set email alerts
|

The shaping and functional consequences of the microRNA landscape in breast cancer

Abstract: MicroRNAs (miRNAs) show differential expression across breast cancer subtypes, and have both oncogenic and tumour-suppressive roles. Here we report the miRNA expression profiles of 1,302 breast tumours with matching detailed clinical annotation, long-term follow-up and genomic and messenger RNA expression data. This provides a comprehensive overview of the quantity, distribution and variation of the miRNA population and provides information on the extent to which genomic, transcriptional and post-transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
430
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(460 citation statements)
references
References 29 publications
28
430
0
2
Order By: Relevance
“…In addition, De Rinaldis et al 32 identified a 46-miRNA signature that could be used to differentiate between breast cancer subtypes. Dvinge et al 33 also obtained similar findings in their research. In a meta-analysis of independent trials, van Schooneveld et al described various subtype-specific miRNAs.…”
Section: Mirna and Intrinsic Subtypes Of Breast Cancersupporting
confidence: 72%
“…In addition, De Rinaldis et al 32 identified a 46-miRNA signature that could be used to differentiate between breast cancer subtypes. Dvinge et al 33 also obtained similar findings in their research. In a meta-analysis of independent trials, van Schooneveld et al described various subtype-specific miRNAs.…”
Section: Mirna and Intrinsic Subtypes Of Breast Cancersupporting
confidence: 72%
“…Invasive lung carcinoma is characterised by the presence of many various genetic and epigenetic alterations in tumour cells [80]. This leads to deregulated expression of certain miRNAs [81], resulting in significant changes in their concentrations and compositions and, consequently, their activities (described as miRNA under-or overexpression), and these miRNAs are potential biomarkers of clinical relevance [82,83]. Previous studies have confirmed the usefulness of miRNAs as biomarkers of NSCLC [48,[84][85][86].…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
“…(A) Kaplan-Meier analysis based on the MetaBriC mir expression data. 43 Survival of the 370 patients with the highest (top third) expression levels of mir-10b* (red line) was compared with the 370 patients with the lowest expression levels (blue line). the plot was truncated at 15 y, P value is indicated in the title.…”
Section: Microrna-10b*mentioning
confidence: 99%